A Multi-Informant Study of the Role of Household Disorder in Low Self-Control. (December 2018) - Jackson, Dylan B.; Vaughn, Michael G.
The current study expands upon Gottfredson and Hirschi's (1990) General Theory of Crime by examining associations between multiple forms of household disorder and low self-control, as well as the potential for attenuated informal social controls within the home to account for these associations. Multi-informant data from the Fragile Families & Child Wellbeing Study (FFCWS) are employed in the present study. Multiple regression-based techniques (e.g., negative binomial regression, logistic regression) are executed in a stepwise fashion to address our research questions. The findings indicate that one form of household disorder in particular, Household Health/Safety Hazards, yielded significant associations with low self-control across multiple model specifications. Informal social control exerted by parents within the home did not appear to explain this relationship. Future research should consider the possibility that certain forms of disorder in the immediate ecological context of the home may attenuate self-control and should explore other potential explanations of the findings.